2013
DOI: 10.1002/glia.22510
|View full text |Cite
|
Sign up to set email alerts
|

Molecular definition of the pro‐tumorigenic phenotype of glioma‐activated microglia

Abstract: Microglia are myeloid cells residing in the central nervous system that participate in inflammatory responses and could promote injury and repair. Gliomas attract microglia and polarize them into tumor-supporting cells that participate in matrix remodeling, invasion, angiogenesis, and suppression of adaptive immunity. Although signaling pathways and critical regulators underlying classical inflammation are well established, signal transduction and transcriptional circuits underlying the alternative activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 66 publications
3
111
2
Order By: Relevance
“…[125][126][127] In a recent study, PAM signaling was upregulated in microglial cells that were exposed to glioma derived factors, indicating that PAM signaling is needed to force microglial cells into a tumor supportive M2 state. [128] This result was supported by a report showing that mTOR inhibition with rapamycin polarizes microglia cells to express a tumor suppressive M1 phenotype. [129] To date, the exact molecular mechanism by which PI3K signaling contributes to M2-polarization of microglia is still unknown and should be the subject of further investigation.…”
Section: Pi3ks In Inflammation/ Microenvironmentmentioning
confidence: 68%
“…[125][126][127] In a recent study, PAM signaling was upregulated in microglial cells that were exposed to glioma derived factors, indicating that PAM signaling is needed to force microglial cells into a tumor supportive M2 state. [128] This result was supported by a report showing that mTOR inhibition with rapamycin polarizes microglia cells to express a tumor suppressive M1 phenotype. [129] To date, the exact molecular mechanism by which PI3K signaling contributes to M2-polarization of microglia is still unknown and should be the subject of further investigation.…”
Section: Pi3ks In Inflammation/ Microenvironmentmentioning
confidence: 68%
“…Gene set enrichment analysis (GSEA) identified hallmarks of biological states or processes enriched in glioblastoma patient CD14 + blood cells relative to healthy donors, including transcriptional regulation by MYC and E2F, protein secretion, oxidative phosphorylation, and fatty acid metabolism (Figure 1D). MYC has previously been shown to have a role in tumor-supportive microglia (24), and E2F is involved in macrophage differentiation (25). GSEA enrichment plots and expression heat maps are shown in Supplemental Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this hypothesis, Kaminska and co-workers reported that glioma-derived soluble factors induce the activation of focal adhesion kinase, PI3K (phosphoinositide 3-kinase)/Akt (protein kinase B), ERK (extracellular-signal-regulated kinase), and P38 MAPK (mitogen-activated protein kinase) signaling pathways, resulting in enhancement of cell motility, phagocytosis, sustained proliferation and a distinct genomic response. Such activated microglial phenotype appeared to be unique, being not associated with activation of NFκB (nuclear factor κB) and Stat1 and thus up-regulation of inflammatory genes (Ellert-Miklaszewska et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that intra-tumoral microglia express an M2 phenotype in response to soluble factors released by glioma cells. For example, Kaminska and co-workers have recently characterized the M2 activation state of rat microglia cells exposed to a conditioned medium harvested by rat C6 glioma cell cultures as well as the molecular pathways that direct microglia toward a pro-invasive and immunosuppressive phenotype (Gabrusiewicz et al, 2011; Ellert-Miklaszewska et al, 2013). Using co-cultures of the human microglia cell line CHME-5 and the rat glioma C6 cells, Bouzier-Sore and co-workers showed that microglial activation after exposure to C6 cells is bi-phasic, with a prior transitory phagocytic activated phenotype (M2) followed by a reversal to a non-phagocytic status (M1) (Voisin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%